Secreted Virulence Factor Comparison Between Methicillin-Resistant and Methicillin-Sensitive Staphylococcus aureus, and its Relevance to Atopic Dermatitis - Schlievert, Patrick M. (2010)
Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) strains have emerged as serious health threats in the last 15 years. They are associated with large numbers of atopic dermatitis skin and soft tissue infections, but also originating from skin and mucous membranes, have the capacity to produce sepsis and highly fatal pulmonary infections characterized as necrotizing pneumonia, purpura fulminans, and post-viral TSS. This review is a discussion of the emergence of three major CA-MRSA organisms, designated CA-MRSA USA400, followed by USA300, and most recently USA200. CA-MRSA USA300 and USA400 isolates and their methicillin-sensitive counterparts (CA-MSSA) typically produce highly inflammatory cytolysins α-toxin, γ-toxin, δ-toxin (as representative of the phenol soluble modulin family of cytolysins), and Panton Valentine leukocidin. USA300 isolates produce the superantigens enterotoxin-like Q and a highly pyrogenic deletion variant of toxic shock syndrome toxin-1 (TSST-1), whereas USA400 isolates produce the superantigens staphylococcal enterotoxin (SE) B or SEC. USA200 CA-MRSA isolates produce small amounts of cytolysins but produce high levels of TSST-1. In contrast, their MSSA counterparts produce various cytolysins, apparently in part dependent on niche occupied in the host, and levels of TSST-1 expressed. Significant differences seen in production of secreted virulence factors by CA-MRSA versus hospital-associated MRSA and CA-MSSA strains appear to be due to the need to specialize as the result of energy drains from both virulence factor production and methicillin-resistance.